Respuestas
Respuesta dada por:
4
P= 2\pi * r
A = \pi *r²
121 \pi = \pi *r²
r²= (121\pi) / (\pi ) Se simplifica \pi
√r² = √121
r = 11
P= 2\pi * r
P = 2\pi * (11)
P= 22\pi
P= 69.11 cm
A = \pi *r²
121 \pi = \pi *r²
r²= (121\pi) / (\pi ) Se simplifica \pi
√r² = √121
r = 11
P= 2\pi * r
P = 2\pi * (11)
P= 22\pi
P= 69.11 cm
Respuesta dada por:
1
P= 2\pi * r
A = \pi *r²
121 \pi = \pi *r²
r²= (121\pi) / (\pi ) Se simplifica \pi
√r² = √121
r = 11
P= 2\pi * r
P = 2\pi * (11)
P= 22\pi
P= 69.11 cm
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años
hace 10 años